Graphene oxide and reduced graphene oxide induced neural pheochromocytoma-derived PC12 cell lines apoptosis and cell cycle alterations via the ERK signaling pathways - Kang YY (Dove Medical Press, 2017)
Yiyuan Kang, Jia Liu, Junrong Wu, Qian Yin, Huimin Liang, Aijie Chen, Longquan Shao Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of China Abstract: Given the novel applications of graphene materials in biomedical and electronics industry, the health hazards of these particles have attracted extensive worldwide attention. Although many studies have been performed on graphene material-induced toxic effects, toxicological data for the effect of graphene materials on the nervous system are lacking. In this study, we focused on the biological effects of graphene oxide (GO) and reduced graphene oxide (rGO) materials on PC12 cells, a type of traditional neural cell line. We found that GO and rGO exerted significant toxic effects on PC12 cells in a dose- and time-dependent manner. Moreover, apoptosis appeared to be a response to toxicity. A potent increase in the number of PC12 cells at G0/G1 phase after GO and rGO exposure was detected by cell cycle analysis. We found that phosphorylation levels of ERK signaling molecules, which are related to cell cycle regulation and apoptosis, were significantly altered after GO and rGO exposure. In conclusion, our results show that GO has more potent toxic effects than rGO and that apoptosis and cell cycle arrest are the main toxicity responses to GO and rGO treatments, which are likely due to ERK pathway regulation. Keywords: graphene oxide, reduced graphene oxide, PC12, cell cycle alterations, ERK pathway